2012
DOI: 10.1111/j.1365-2109.2012.03214.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization by refrigerator stored sperm of the Indian major carp,Labeo calbasu(Hamilton, 1822)

Abstract: This study reports on the spermatological properties, and on the development of a protocol for refrigerator storage (4°C) of Labeo calbasu (Hamilton, 1822) sperm for artificial breeding. Volume, motility, concentration and pH of the freshly collected sperm were 2.21 ± 0.53 (μL g−1 of fish weight) (mean ± SD), 95 ± 1 (%), 1.93 ± 0.44 × 109 (cells mL−1) and 7.56 ± 0.17 respectively. Sperm activation was evaluated at different osmolalities of NaCl solution, and motility ceased completely when osmolality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…Sperm concentration might be related to gonadal development and maturation, which are also regulated by changing in climate, day food length and food supply (Piros et al 2002). The present study showed that the sperm density (3.14±0.165× 10 10 /ml) of B. gonionotus was similar to Hypophthalmicthys molitrix (Rahman et al, 2011), however, higher compared to L. calbasu (Hassan et al, 2013) and salmonid fish (Hatef et al, 2007). Sperm density of Salmo trutta abanticus (Hatipoglu and Akcay, 1954) and Salmo trutta macrostigma (Yavas et al, 2015) were 17.9×10 9 /ml and 14.53×10 9 / ml, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Sperm concentration might be related to gonadal development and maturation, which are also regulated by changing in climate, day food length and food supply (Piros et al 2002). The present study showed that the sperm density (3.14±0.165× 10 10 /ml) of B. gonionotus was similar to Hypophthalmicthys molitrix (Rahman et al, 2011), however, higher compared to L. calbasu (Hassan et al, 2013) and salmonid fish (Hatef et al, 2007). Sperm density of Salmo trutta abanticus (Hatipoglu and Akcay, 1954) and Salmo trutta macrostigma (Yavas et al, 2015) were 17.9×10 9 /ml and 14.53×10 9 / ml, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Yavas et al (2015) reported that motility duration of Salmo trutta macrostigma was 68.1s. Hassan et al (2013) observed that L. calbasu sperm remained motile for 138s after activated with 0.3% NaCl solution. The individual variation of sperm motility and duration depends on the age of male fish (Tekin et al, 2003) and time of season (Akcay et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations